The Intensity Influence Of Accessing Instagram @Ala_Santri On The Lifestyle Of Students At Al-Muhsin Islamic Boarding School, Sleman, Yogyakarta - Achmad Zaky Faiz; Khoirotun Nisa (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
The article aims to find out if there is any impact between the intensity of accessing instagram reasons. An id against the lifestyle of santri bool-hut al-muhsin depok sleman yogyakarta. As for the theory used in this study, it's the use and effect theory that represents the use and effect. Validity and reliability tests are calculated using version 15 SPSS. The method used in this study is a quantitative approach, with the survey method in which the data collection technique USES a questionnaire in 54 people santri al-muhsin depok sleman yogyakarta. Where the sample taking techniques USES the saturated sampling technique, so that the entire population that has filled the responders are sample taken. The processing of the data in this study USES a likert scale and a hypothetical result with a Pearson's product moment correlation analysis indicates that there is a.500 correlation of 0.250 with dk = 52 (n-2/54-2) so 0.500> 0.250 (rcount> rtable) and p = 0.000 (p > 0.05), which means that there is an effect of accessing the @alasantri.id Instagram account on the lifestyle of the students of the Al-Muhsin Islamic Boarding School, Depok, Sleman, Yogyakarta.